Changes in Deep Water Oxygenation of the South China Sea Since the Last Glacial Period. Issue 17 (5th September 2018) - Li, Gang; Rashid, Harunur; Zhong, Lifeng; Xu, Xing; Yan, Wen; Chen, Zhong
Abstract: The Pacific meridional overturning circulation is thought to have a significant influence on global climate. However, the extent to which intermediate and deep circulations have changed in the Pacific Ocean since the Last Glacial Maximum (LGM) is not well known. At present, the South China Sea Deep Water (SCSDW) is fed by the upper Pacific Deep Water. Here we present new benthic foraminiferal δ 13 C and redox‐sensitive elemental data from a sediment core retrieved from the southern deep SCS to reconstruct the oxygenation history of the SCSDW since the LGM. Oxygenation records from the deep SCS and intermediate and deep waters in the Pacific Ocean demonstrate that the SCSDW deeper than 1, 600 m has been sourced by the Pacific Deep Water since the LGM. Our data suggest that the well‐ventilated North Pacific Intermediate Water would not have influenced the SCSDW during cold stadials of the last deglacial period. Plain Language Summary: The global ocean circulation has an important role in influencing the climate. Large‐scale change in global ocean circulation has occurred since the last glacial period. In comparison to the Atlantic Ocean, oxygenation data from the intermediate and deep waters of the Pacific Ocean are relatively poor. At present, the South China Sea Deep Water (SCSDW) is mainly fed by the Pacific Deep Water. In this contribution, we present new carbon isotope data on bottom‐water‐living protists and abundance of redox‐sensitive elements that highlight the availability of oxygen from a sediment core in the southern deep SCS. The data allow reconstruction of the oxygenation history of the SCSDW for the past 30, 000 years. Our data are compared with other published oxygenation records from intermediate and deep waters in the Pacific Ocean. The combined oxygenation records demonstrate that the SCSDW would have been sourced by the Pacific Deep Water since the Last Glacial Maximum (21, 000 years before present). The oxygenation records in the deep SCS appear to support the general circulation model results and paleo‐proxy data in the North Pacific, which suggest that a strengthened meridional overturning mainly occurred within intermediate waters during cold stadials of the last deglacial period. Key Points: Deep water oxygenation changes in the South China Sea since the last glacial period have mirrored those in Pacific deep water The strengthened North Pacific Intermediate Water did not influence South China Sea deep water during cold stadials of the last deglacial period A strengthened intermediate‐depth meridional overturning occurred in the western Pacific Ocean during cold stadials of the last deglacial period